The effect of heat shock on myogenic differentiation of human skeletal-muscle-derived mesenchymal stem/stromal cells - Mikšiūnas, Rokas; Labeit, Siegfried; Bironaité, Daiva (Cells, 2022)
Muscle injuries, degenerative diseases and other lesions negatively affect functioning of human skeletomuscular system and thus quality of life. Therefore, the investigation of molecular mechanisms, stimulating myogenic differentiation of primary skeletal-muscle-derived mesenchymal stem/stromal cells (SM-MSCs), is actual and needed. The aim of the present study was to investigate the myogenic differentiation of CD56 (neural cell adhesion molecule, NCAM)-positive and -negative SM-MSCs and their response to the non-cytotoxic heat stimulus. The SM-MSCs were isolated from the post operation muscle tissue, sorted by flow cytometer according to the CD56 biomarker and morphology, surface profile, proliferation and myogenic differentiation has been investigated. Data show that CD56(+) cells were smaller in size, better proliferated and had significantly higher levels of CD146 (MCAM) and CD318 (CDCP1) compared with the CD56(−) cells. At control level, CD56(+) cells significantly more expressed myogenic differentiation markers MYOD1 and myogenin (MYOG) and better differentiated to the myogenic direction. The non-cytotoxic heat stimulus significantly stronger stimulated expression of myogenic markers in CD56(+) than in CD56(−) cells that correlated with the multinucleated cell formation. Data show that regenerative properties of CD56(+) SM-MSCs can be stimulated by an extracellular stimulus and be used as a promising skeletal muscle regenerating tool in vivo.
This article belongs to the Special issue: Regulation mechanisms of myogenic and cardiomyogenic differentiation
Gesehen am 15.08.2023